Finland : Selected Issues. (IMF Staff Country Reports; Country Report, 1999)
This Selected Issues paper outlines Finland's experience in the field of public expenditure policies, illustrates alternative medium-term approaches to fiscal policy, and discusses prospects for efficient expenditure management in the future. The paper illustrates the evolution of public expenditures from the creation of the welfare state to the crisis of the early 1990s. It discusses the post-crisis consolidation process, including the institutional reforms that facilitated adjustment. The paper also illustrates the future challenges and policy trade-offs in the context of alternative long-term scenarios.